Avaliação de diferentes estratégias de determinação de nutrientes e potenciais contaminantes em alimentos por técnicas baseadas em laser - Augusto, Amanda dos Santos (Universidade Federal de São Carlos, 2018)
The present project focuses on the development of strategies for the elemental determination of Ca, Cd, Cr, Cu, Fe, Mg, Pb and Zn in samples of orange juice and dietary supplements by Laser-Induced Breakdown Spectroscopy (LIBS). For the determination of the analytes studied in supplements, by LIBS, several calibration methods were evaluated: the external calibration where cellulose was used and the samples themselves as the basis for the production of solid reference materials, PLS (Partial Least Squares ) as a multivariate calibration option and the calibration called MEC (Multi - Energy Calibration). Juice samples and aqueous standards were immobilized on a thin polymer film of PVA (Polyvinyl Alcohol) and analyzed by LIBS and LA-ICP-MS. In the analyzes by LIBS even with the conversion of the sample from the liquid to the solid state and/or with the DLLME (Dispersive Liquid-Liquid Micro Extraction) method, in different supports, it was not possible to obtain signals of intensity sufficiently intense for the analyzed analytes. During the implementation of this project it was possible to hold a one-year internship at the Lawrence Berkeley National Laboratory under the supervision of Dr. Richard Russo. In this part of the work dietary supplements were analyzed, but using a LIBS / LA-ICP OES (Laser Ablation Inductively Coupled Plasma Optical Emission) in order to propose a protocol of direct analysis of solids. Chemometrics was applied throughout the project to optimize the analytical conditions and identify the best working conditions. Chemometric tools were also used to generate calibration models for the rapid determination of the analytes.
Evaluation of different strategies for nutrient and potential contaminants determination in foods by laser-based techniques
Keywords: Laser; LIBS; LA-ICPOES; LA-ICP-MS; Calibração; Alimentos; Análise direta; Nutrientes; Laser; Calibration; Food; Direct analyze; Nutrients; CIENCIAS EXATAS E DA TERRA::QUIMICA